PENYELESAIAN SENGKETA MEDIS KESALAHAN DIAGNOSIS - Metha Dian Puspa Nasawida; Siti Hatika Sari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Misdiagnosis or wrong diagnosis means that a person is given a diagnosis of a certain disease but does not actually experience the disorder. Not only in Indonesia, this also often happens abroad. Similar terms and conditions are termed pit fall diagnosis, overdiagnosis or misdiagnosis. Methods This research uses empirical normative legal research. MKEK only decides on the ethical issue of the medical profession, considering its capacity which is not a medical court institution that is legally authorized to decide whether a misdiagnosis is classified as medical malpractice or medical negligence. At best the MKEK can only provide a statement whether a doctor who made a misdiagnosis has taken medical action in accordance with the legislation, in this case the Health Law, KODEKI and existing Medical Professional Standards or not